Characteristics of Lake Ohrid - Belichovska Katerina, Belichovska Daniela (Institute of Knowledge Menagament, Skopje, 2016)
Lake Ohrid is a rare natural phenomenon of tectonic origin. It is one of the oldest oligotrophic lakes in the world. It represents a complex ecological system, where its wildlife takes a special role. According to its geomorphological and biological values it represents a unique entity in which part of the old tertiery world with its numerous archaic forms, such as relics and endemics is preserved. In this paper, numbers of scientific findings on the characteristics of the Lake Ohrid are reviewed.
Keywords: Lake Ohrid, basic characteristics